Combination of humectants with potassium sorbate and sodium benzoate to inhibit Curvularia clavata contamination in Thai Fermented Fish Spicy Dip (Nam Phrik Pla Ra) - Khuenpet, K.; Srapinkornburee, W.; Tassanaudom, U. (International Journal of Agricultural Technology, 2021)
Samples of Thai fermented fish spicy dip (nam phrik pla ra) had a high total viable count and high yeast and mold counts of 4.6 and 2.2 log CFU/g, respectively, that exceeded the standard values set by the Thai Industrial Standards Institute (TISI) of less than 4 and 2 log CFU/g, respectively. Sample isolation and identification revealed that Curvularia clavata (isolate 518) was the highest contaminating species. Glucose syrup (5%) should be used in chili paste production to reduce its aw and to extend the shelf life of nam phrik pla ra (5 days) and not exceed the standards set by the TISI. C. clavata growth was inhibited by adding humectants and preservatives to the sample. The shelf life of nam phrik pla ra containing 5% glycerol with 500 mg/kg potassium sorbate was 7 days, while adding 5% glucose syrup with 500 mg/kg potassium sorbate could prolong the shelf life to longer than 14 days